The Effect of Resection Angle on Stress Distribution after Root-End Surgery - Monteiro, Jaiane Bandoli; Dal Piva, Amanda Maria Oliveira; Tribst, JoÃ£o Paulo Mendes; Borges, Alexandre Luiz Souto; Tango, Rubens Nisie (Iranian Endodontic Journal, 2018)
Introduction: This study aimed to investigate the influence of the resection angle on the stress distribution of retrograde endodontic treated maxillary incisors under oblique-load application. Methods and Materials: A maxillary central incisor which was endodontically treated and restored with a fiber glass post was obtained in a 3-dimensional numerical model and distributed into three groups according to type of resection: control; restored with fiber post without retrograde obturation, R45 and R90 with 45º and 90º resection from tooth axial axis, respectively and restored with Fuji II LC (GC America). The numerical models received a 45º occlusal load of 200 N/cm2 on the middle of lingual surface. All materials and structures were considered linear elastic, homogeneous and isotropic. Numerical models were plotted and meshed with isoparametric elements, and the results were analyzed using maximum principal stress (MPS). Results: MPS showed greater stress values in the bone tissue for control group than the other groups. Groups with apicectomy showed acceptable stress distribution on the fiber post, cement layer and root dentin, presenting more improved values than control group. Conclusion: Apicectomy at 90º promotes more homogeneity on stress distribution on the fiber post, cement layer and root dentin, which suggests less probability of failure. However, due to its facility and stress distribution also being better than control group, apicectomy at 45° could be a good choice for clinicians. Keywords: Apicectomy; Cut Angle; Dental Stress Analysis; Endodontics; Finite Element Analysis; Resection Angle